A recombinant porcine reproductive and respiratory syndrome virus type 2 field strain derived from two PRRSV-2-modified live virus vaccines - Trevisan, Giovani; Magstadt, Drew; Woods, Amy; Sparks, Joel; Zeller, Michael; Li, Ganwu; Krueger, Karen M.; Saxena, Anugrah; Zhang, Jianqiang; Gauger, Phillip C. (Frontiers in Veterinary Science, 2023)
A porcine reproductive and respiratory syndrome virus (PRRSV) type 2 (PRRSV-2) isolate was obtained from lung samples collected from a 4.5-month-old pig placed in a wean-to-finish site located in Indiana, United States of America (USA), although no gross or microscopic lesions suggestive of PRRSV infection were observed in lung tissue. Phylogenetic and molecular evolutionary analysis based on the obtained virus sequences indicated that the isolate PRRSV USA/IN105404/2021 was a natural recombinant from Ingelvac PRRS® MLV and Prevacent® PRRS, both PRRSV-2 modified live virus vaccines commercially available in the USA. This study is the first to report the detection of a PRRSV-2 recombinant consisting entirely of 2 modified live virus vaccine strains under field conditions. Based on clinical data and the absence of lung lesions, this recombinant PRRSV-2 strain was not virulent in swine, although its pathogenicity needs to be confirmed by a clinical trial.